Kirchnerismo y discurso fundacional: los editoriales de la agrupación juvenil La Cámpora - Flax, Rocío (2018)
This work is part of a research project that seeks to understand, from a linguistic-discursive perspective, the creation and consolidation of the Argentine political group called La Cámpora. This group was organized by former president Nestor Kirchner and nowadays follows the leadership of president Cristina Fernandez. This time, we examine the way the politicalgroup positioned itself as foundational discourse, presenting Kirchner as a complete break with a past presented as disastrous for the country. For this pourpose we will consider two lines of analysis: first, the construction of enemies and, secondly, the use of temporal and spatial expressions dislocated to the left of the clause as a way to reiforce the difference with thepast and the uniqueness of the present.